(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
An original model is proposed for determination of the statically indeterminate tension (internal tensile force) in the blade (saw band) of a horizontal bandsaw with a tensioning spring mechanism. The statically indeterminate problem is solved in a way missing in the bandsaw references but required by the Strength of Materials science: based on a deformation compatibility equation. In the case considered, in that equation the spring parameters are also involved. The model proposed is a generalization of a published previous model (Stefanov 2013) regarding a vertical bandsaw blade tension.